2009
DOI: 10.1086/595299
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Presentation, and Outcome of Progressive Multifocal Leukoencephalopathy in HIV-Infected Patients during the Highly Active Antiretroviral Therapy Era: A Nationwide Cohort Study

Abstract: The incidence of PML in HIV-infected patients decreased after the introduction of HAART. Survival after PML remains poor. In the management of PML, the main focus should be on prophylactic measures to avoid immunodeficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
143
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(158 citation statements)
references
References 23 publications
10
143
3
2
Order By: Relevance
“…Bad prognostic indicators include a CD 4 count of less than 100/µL associated with other opportunistic infections [14]. There is no effective treatment for PML but with the advent of ART, the prognosis may be better [15][16][17]. Cidofovir and camptothecin are two new drugs which are being used in controlled clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bad prognostic indicators include a CD 4 count of less than 100/µL associated with other opportunistic infections [14]. There is no effective treatment for PML but with the advent of ART, the prognosis may be better [15][16][17]. Cidofovir and camptothecin are two new drugs which are being used in controlled clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in HIV patients, PML often arises in severe immunocompromised states, when CD4 T cell count is lower than 200/mm 3 . Nevertheless, cases have been described with CD4 T cell count higher than that value [4,5,7,9]. Yet, case reports of definite PML with more than 500/mm 3 CD4 T cell count are quite rare.…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection accounts for 85% of all cases of PML, with a prevalence estimated of 4-5% in this population [1,3]. The probability of an HIV patient developing neurological symptoms and PML lesions is higher amongst the ones with a lower immunological status, expressed by a CD4 T cell count lower than 200/mm 3 [4,5]. There are very few reports of PML among HIV infected patients with a better immunological condition, with more than 500 CD4/mm 3 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In HIV-positive patients with PML, the prognosis has been improving since the introduction of cART. Recent reports have shown that recovery of immune response induced by cART improve the prognosis in HIVpositive patients with PML [21,22].…”
Section: Prognosismentioning
confidence: 99%
“…The prevalence of PML increased substantially during HIV epidemic and mortality related to PML has also increased in the post-HIV era. However, the restoration of immune response by combination antiretroviral therapy (cART) has shown to induce the improvement of prognosis of PML [4]. Recently, immunomodulatory medications which suppress the host cellular immune response, such as nantalizumab for multiple sclerosis and rituximab for malignant lymphoma are associated with PML [5,6].…”
Section: Introductionmentioning
confidence: 99%